Germination requirements of Plantago algarbiensis seeds, an endangered species endemic to the Algarve region (South of Portugal) - Martins, Neusa (2015)
The ecdysteroid, 20-hydroxyecdysone or beta-ecdysone, is a steroid hormone which plays a crucial role in molting, metamor- phosis and reproduction of arthropods. This ecdysteroid and its analogues have high potential to be used as insecticides. Previous studies in our laboratory have demonstrated that Vitex glabrata R.Br. (commonly known as Khai-Nao), an indigenous herbaceous plant of Thailand, synthesized and accumulated high quantity of 20-hydroxyecdysone. Therefore, the aim of this study was to investigate the effect of precursor and elicitors feeding on cell growth and 20-hydroxyecdysone production of V. glabrata suspension cultures. Plant cells were cultured in half strength MS medium containing 30 g/l glucose and supplemented with 2.0 mg/l 6- benzylaminopurine (BAP) and 1.0 mg/l 2,4-dichlorophenoxyacetic acid (2,4-D). Cells were incubated on a rotary shaker at 120 rpm under continuous light of 2000 lux at 25 °C. Sterilized cholesterol (5 and 10 mg/l) as precursor was added to the cell cultures on the day of inoculation, while chitosan (50, 100 and 200 mg/l) and methyl jusmonate (100 and 200 mM) as elicitors were added to the cell cultures on day 6 after cultivation.